2016
DOI: 10.1186/s12888-016-0873-y
|View full text |Cite
|
Sign up to set email alerts
|

Filling the treatment gap: developing a task sharing counselling intervention for perinatal depression in Khayelitsha, South Africa

Abstract: BackgroundPerinatal depression is a major public health issue especially in low income settings in South Africa, where there is a shortage of mental health professionals. New psychological interventions delivered by non-specialists are needed to fill the treatment gap. This paper describes the process of developing a manual based task sharing counselling intervention for perinatal depression in Khayelitsha, Cape Town.MethodsQualitative semi-structured interviews were conducted with 26 participants, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
5
34
0
Order By: Relevance
“…While most of the evidence of the effectiveness of midwife‐led counselling comes from interventions for women with childbirth fear or those who experienced emotional distress at birth (rather than a diagnosed mental health problems), this literature indicates that midwives can deliver counselling interventions with positive outcomes. This is consistent with a growing body of literature that highlights that perinatal mental health interventions can be delivered by non‐specialists with positive outcomes, with evidence from low‐ and middle‐income countries (Nyatsanza, Schneider, Davies, & Lund, ; Rahman et al., ), the volunteer sector (Coe & Barlow, ) and peer support (Jones, Jomeen, & Hayter, ).…”
Section: Discussionsupporting
confidence: 84%
“…While most of the evidence of the effectiveness of midwife‐led counselling comes from interventions for women with childbirth fear or those who experienced emotional distress at birth (rather than a diagnosed mental health problems), this literature indicates that midwives can deliver counselling interventions with positive outcomes. This is consistent with a growing body of literature that highlights that perinatal mental health interventions can be delivered by non‐specialists with positive outcomes, with evidence from low‐ and middle‐income countries (Nyatsanza, Schneider, Davies, & Lund, ; Rahman et al., ), the volunteer sector (Coe & Barlow, ) and peer support (Jones, Jomeen, & Hayter, ).…”
Section: Discussionsupporting
confidence: 84%
“…Feasibility The use of CBT components was shown to be feasible for NSHW delivery by seven studies [2,3,7,10,12,24,27,30,33,40]. The selection of feasible strategies and components was based on piloting/ feasibility studies (n = 4) or qualitative studies (n = 3) involving stakeholders.…”
Section: Key Barriers and Facilitators Across Implementation Outcomesmentioning
confidence: 99%
“…While Chibanda et al [11] and Dawson et al [16] expressed concern about the complexity of the cognitive component of standard CBT, Papas et al [34,35] suggested that its "highly structured format" made Acceptability Five studies reported that acceptable interventions contained beneficial information and skills for the service user and the community [2,3,11,12,24,31]. Some barriers to acceptability were women's lack of autonomy (both as service users and providers), cultural barriers, stigma, lack of engagement and resistance to changes in sociocultural hierarchies [3,33]. Some service users reported concerns about whether their confidentiality would be ensured, especially in group interventions or if there were family members present [2,24].…”
Section: Key Barriers and Facilitators Across Implementation Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…National estimates range from 75 per cent in South Africa [33] to over 90 per cent in Ethiopia [34]. There are a number of studies on depression treatment gap in different sub-Saharan African settings, but these focus on younger age groups and conditions such as postpartum and perinatal depression [35,36].…”
Section: Discussionmentioning
confidence: 99%